Factors influencing aspiring teachers' disposition of online reading - Syamsul Fozy Osman (Kulliyyah of Education, International Islamic University Malaysia, 2018)
The plethora of online reading (OR) materials brought about by the advent of Information and Communication Technology (ICT) is generating transformations in reading trends, behaviors and literacy expectations. Teachers are directly implicated by the change especially since they are recognized contributors to the development of reading habits. However, there is a lack of information on aspiring teachers', as teachers of the future, dispositions upon OR, making it necessary for an investigation to be attempted. Significantly, the results of the study could be an indicator of needs for enhancements in the aspiring teachers' training approach in order to ensure that the teachers produced would fulfill the needs of the society and suited to the progress in the field. Thus, the main purpose of this study is to explore Malaysian aspiring teachers' disposition towards OR and identify the factors influencing the disposition. Founded upon a theoretical framework that synergizes the Hypertext Theory, New Literacies Theory and Self-Determination Theory, the study employs a mixed method approach, specifically the exploratory sequential design in the investigation. Data collection and analysis were done in two components, (1) Qualitative and (2) Quantitative. The qualitative component employed an interview to investigate the thoughts of 14 aspiring teachers informants upon OR. From this component, ten influencing factors were successfully derived using Taylor-Powell and Renner's (2003) steps for qualitative analysis and Hesse-Biber's (2010) coding strategies. The qualitative based factors were then used as the foundation of a questionnaire designed for the quantitative component. The questionnaire, administered to 432 aspiring teachers, resulted with data that was statistically analyzed using exploratory factor analysis and resulted with a conclusive set of ten underlying factors indicative of the aspiring teachers' disposition upon OR. It was concluded that the Malaysian aspiring teachers involved in this study have a positive disposition towards OR and the underlying factors identified as influential towards the disposition could be listed as (1) External support (2) Intrinsic motivation support, (3) Finance and promotions, (4) Practical benefits, (5) Openness and trust, (6) Self educational needs, (7) Future students' needs, (8) Critical thinking and analysis skills enhancements, (9) Future career's needs and (10) Reading interest and enjoyment.